Evaluasi Kinerja Penyuluh Pertanian dalam Mewujudkan Implementasi Paket Teknologi di Kecamatan Makale Kabupaten Tana Toraja - Yosep Paningo; Ibrahim, Helda; nursaman, herman (Lembaga Pengembangan Kinerja Dosen, 2025)
Global challenges such as climate change and land degradation demand the strengthening of the agricultural sector through the adoption of relevant technologies. Agricultural extension plays an important role in conveying information and technological innovations to farmers, with extension workers as facilitators, educators, and motivators in accelerating the implementation of agricultural technology packages. However, the rate of adoption of technology by farmers is still low, especially in Tana Toraja Regency, South Sulawesi. In addition, there is no comprehensive and results-based evaluation system for extension workers. This study aims to determine the level of farmers' understanding of agricultural technology packages introduced by agricultural extension workers in Batu Papan Village, Makale District, Tana Toraja Regency. The research uses a descriptive quantitative approach with the object of the study, namely Field Agricultural Extension Workers (PPL) active in Makale District as many as seven people and 139 assisted farmers from six farmer groups. Farmer samples were taken as much as 20% of the population or 30 respondents using census and purposive sampling techniques. Data collection was carried out through a questionnaire with a Likert scale to assess farmers' perception and level of understanding of the implementation of agricultural technology packages. The results showed that the level of farmers' understanding of the technology package introduced by extension workers was in the